The Effect on Education of Cigarette’s Danger Through Instagram on the Knowledge, Attitudes, and Practices of Female Student Smokers - Swastika, Dita Primanda Arum; Shaluhiyah, Zahroh; Musthofa, Syamsul Huda Budi (Journal of Health Education, 2021)
Background: Smoking behavior in women is a serious health problem. Indonesia is a country that has a fairly high prevalence of female smokers, and is the third country with the highest number of female smokers after Myanmar and Laos. Cigarette advertisements on social media are one of the factors that influence smoking behavior. The number of adolescents who use social media, especially Instagram, can have an influence on smoking behavior. The research aimed to analyze the influence of health education thourgh instagram towards the Diponegoro students knowledge, attitude, and practice of smooking behaviour control. Method: A quasi-experimental study with the design of a pretest-posttest group design by using purposive sampling. The subject is 66 women students of Diponegoro University. Data collected using a questionnaire with data analyzed by Mc Nemar, Wilcoxon, and Mann-Whitney tests. Results: there is an influence of health education using instagram to increase the knowledge (p = 0,000), attitudes (p = 0,005), and practices (p = 0,042) of Diponegoro University students in the smooking behavior control. Conclusions: Health education through Instagram has an effect on the knowledge, attitudes, and practices of female student smoking behavior control.